A particular silent codon exchange in a recombinant gene greatly influences host cell metabolic activity. Issue 1 (December 2015) - Rahmen, Natalie; Schlupp, Christian; Mitsunaga, Hitoshi; Fulton, Alexander; Aryani, Tita; Esch, Lara; Schaffrath, Ulrich; Fukuzaki, Eiichiro; Jaeger, Karl-Erich; Büchs, Jochen
Abstract Background Recombinant protein production usingEscherichia coli as expression host is highly efficient, however, it also induces strong host cell metabolic burden. Energy and biomass precursors are withdrawn from the host's metabolism as they are required for plasmid replication, heterologous gene expression and protein production. Rare codons in a heterologous gene may be a further drawback. This study aims to investigate the influence of particular silent codon exchanges within a heterologous gene on host cell metabolic activity. Silent mutations were introduced into the coding sequence of a model protein to introduce all synonymous arginine or leucine codons at two randomly defined positions, as well as substitutions leading to identical amino acid exchanges with different synonymous codons. The respectiveE. coli clones were compared during cultivation in a mineral autoinduction medium using specialized online and offline measuring techniques to quantitatively analyze effects on respiration, biomass and protein production, as well as on carbon source consumption, plasmid copy number, intracellular nucleobases and mRNA content of each clone. Results Host stain metabolic burden correlates with recombinant protein production. Upon heterologous gene expression, tremendous differences in respiration, biomass and protein production were observed. According to their different respiration activity theE. coli clones could be classified into two groups, Type A and Type B. Type A clones tended to higher product formation, Type B clones showed stronger biomass formation. Whereas codon usage and intracellular nucleobases had no influence on the Type-A–Type-B-behavior, plasmid copy number, mRNA content and carbon source consumption strongly differed between the two groups. Conclusions Particular silent codon exchanges in a heterologous gene sequence led to differences in initial growth of Type A and Type B clones. Thus, the biomass concentration at the time point of induction varied. In consequence, not only plasmid copy number and expression levels differed between the two groups, but also the kinetics of lactose and glycerol consumption. Even though the underlying molecular mechanisms are not yet identified we observed the astonishing phenomenon that particular silent codon exchanges within a heterologous gene tremendously affect host cell metabolism and recombinant protein production. This could have great impact on codon optimization of heterologous genes, screening procedures for improved variants, and biotechnological protein production processes.